Expresión 8: "y" equals "x" plus 6 left brace, negative 5 less than or equal to "x" less than or equal to negative 3 , right bracey=x+6−5≤x≤−3
8
Expresión 9: "y" equals negative "x" left brace, negative 3 less than or equal to "x" less than or equal to negative 1 , right bracey=−x−3≤x≤−1
9
Expresión 10: "y" equals "x" left brace, 1 less than or equal to "x" less than or equal to 3 , right bracey=x1≤x≤3
10
Expresión 11: "y" equals negative "x" plus 6 left brace, 3 less than or equal to "x" less than or equal to 5 , right bracey=−x+63≤x≤5
11
Expresión 12: "y" equals 1 left brace, 1 less than or equal to "x" less than or equal to 5 , right bracey=11≤x≤5
12
Expresión 13: "y" equals 1 left brace, negative 5 less than or equal to "x" less than or equal to negative 1 , right bracey=1−5≤x≤−1
13
Expresión 14: "y" equals negative .1 2 "x" squared plus 8.5 left brace, negative 7 less than or equal to "x" less than or equal to 7 , right bracey=−.12x2+8.5−7≤x≤7
14
Expresión 15: "y" equals negative .2 5 "x" squared minus 1 left brace, negative 2 less than or equal to "x" less than or equal to 2 , right bracey=−.25x2−1−2≤x≤2